Cloning and Analysis of Gene Expression of Two Toll Receptors in Freshwater Pearl Mussel Hyriopsis cumingii - Huang, Ying; Han, Keke; Ren, Qian (Frontiers in Physiology, 2018)
Toll receptors are involved in innate immunity of invertebrates. In this study, we identify and characterize two Toll genes (named HcToll4 and HcToll5) from triangle sail mussel Hyriopsis cumingii. HcToll4 has complete cDNA sequence of 3162 bp and encodes a protein of 909 amino acids. HcToll5 cDNA is 4501 bp in length and encodes a protein of 924 amino acids. Both deduced HcToll4 and HcToll5 protein contain signal peptide, extracellular leucine rich repeats, and intracellular Toll/interleukin-1 receptor domains. Quantitative real-time PCR analysis revealed that HcToll4 and HcToll5 were largely distributed in the hepatopancreas and could be detected in the gills and mantle. HcToll4 and HcToll5 expression could respond to Staphylococcus aureus, Vibrio parahaemolyticus, White spot syndrome virus or Poly I:C challenge. RNA interference by siRNA results showed that HcToll4 and HcToll5 were involved in the regulation of theromacin (HcThe) and whey acidic protein (HcWAP) expression. Based on these results, HcToll4 and HcToll5 might play pivotal function in H. cumingii innate immune response.